Biodiversity of the genus Oedogonium Link ex Hirn 1900 in Raigad District, Maharashtra, India - Samruddha Phadnis; Ganesh Iyer (International Journal of Life Sciences, 2016)
In this paper, the biodiversity of the genus Oedogonium Link ex Hirn 1900 in Raigad district was studied. During the study of filamentous green algae of Raigad district, 18 taxa of Oedogonium Link ex Hirn were recorded. Of these one species Oedogonium boscii var. notabile is probably recorded for the first time in India.